2020
DOI: 10.1021/acs.jpcb.0c00413
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of N-Isopropylacrylamide in Water: Insight from Experiments, Simulations, and Kirkwood–Buff Analysis Teamwork

Abstract: The behavior of thermoresponsive polymer poly(Nisopropylacrylamide) (PNiPAM), an essential building block in the design of smart soft materials, in aqueous solutions has attracted much interest, which contrasts with our knowledge of Nisopropylacrylamide (NiPAM) monomer. Strikingly, the physicochemical properties of aqueous NiPAM are similarly rich, and their understanding is far from being complete. This stems from the lack of accurate thermodynamic data and quantitative model for atomistic simulations. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
(124 reference statements)
0
14
0
Order By: Relevance
“…This may lead to shifted thermosensitive behavior, as already reported by the referenced studies. 72 , 73 We furthermore believe, that the strength of the polymer–polymer and polymer–solvent bonds may be influenced by sterical hindrance, i.e., binding partners with high affinity may not get into close contact for geometrical reasons. This would not be contradicted by the known effect of the tacticity on the thermosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to shifted thermosensitive behavior, as already reported by the referenced studies. 72 , 73 We furthermore believe, that the strength of the polymer–polymer and polymer–solvent bonds may be influenced by sterical hindrance, i.e., binding partners with high affinity may not get into close contact for geometrical reasons. This would not be contradicted by the known effect of the tacticity on the thermosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Paulo et al found that the collapse of PNIPAM chain at high temperatures is related to the reduced coordination of both amide group and isopropyl group with water, and is observed together with an increase in the monomer–monomer hydrogen bond [ 35 ]. The thermodynamics of NIPAM monomer was investigated by Heyda et al [ 36 ], which could allow for better control of PNIPAM phase behavior. Nellas and coworkers performed a molecular dynamics simulation of pentamer PNIPAM [ 37 ], and they suggest a clathrate-like behavior in the coordinate shell might be responsible for the LCST behavior of PNIPAM.…”
Section: Thermogelling Mechanism/thermogelling Propertiesmentioning
confidence: 99%
“…These should be sufficiently accurate to reproduce experimental data, such as the enthalpy of the coil–globule transition, which depends on the strength of the hydrogen bonds between polymer and water. While this accuracy has been achieved for PNIPAM, 66,86 no further studies have been reported to our knowledge that validate force fields for responsive polymer systems based on different chemical constituents. Therefore, experiments and simulations should go hand in hand to investigate effects related to cononsolvency beyond the application to PNIPAM.…”
Section: Introductionmentioning
confidence: 89%